Pragmatisasi Pendidikan dalam Dunia Kerja - Malikah, Nurul (Nadwa, 2014)
Vocational education as a part of the National Education system plays a strategic role for the realization of the skilled national labor. Because each vocational graduates is created to become good human resources, in the sense that when theyhave completed vocational school they able to apply the knowledge. But in fact, the graduates of vocational school is recognized only by itself school and still lack confidence in the business and industrial world. The old model of vocational education has disadvantage, is education model that was conducted unilaterally so that students left behind by the progress of the business/industrial world. Creating creativity and independence of the student is the right answer to avoiddependency and to reduce the unemployment rate. The Awareness of selfdevelopment by enhancing the students' confidence and self-reliance is an important part to prepare for the long-term goal achievement. AbstrakPendidikan kejuruan sebagai salah satu bagian dari sistem Pendidikan Nasional, memainkan peran yang sangat strategis bagi terwujudnya angkatan tenaga kerja nasional yang terampil. Karena setiap lulusan SMK memang diciptakan untuk menjadi sumber daya manusia yang siap pakai, dalam arti ketika mereka telah menyelesaikan sekolahnya mereka dapat menerapkan ilmu yang telah merekadapat sewaktu di sekolah. Namun pada kenyataannya, tamatan SMK hanya diakui oleh sekolah sendiri dan masih minimnya kepercayaan dunia usaha dan duniaindustri. Pendidikan kejuruan model lama memiliki kelemahan yaitu, penyelenggaraan pendidikan secara sepihak sehingga anak didik tertinggal oleh kemajuan dunia usaha/dunia industri. Menciptakan kreativitas dan kemandirian siswa, merupakan jawaban tepat untuk menghindari ketergantungan dan dapat mengurangi tingkat pengangguran. Kesadaran mengembangkan diri dengan meningkatkan kepercayaan dan kemandirian siswa, merupakan bagian penting untuk mempersiapkan pencapaian tujuan jangka panjang.